Euclid’s Dilemma - Rhyal, Megan (Ohio Journal of School Mathematics, 2018)
This picture book describes an event that potentially took place within the relationship between King Ptolemy and Euclid of Alexandria. Unfortunately, very little is known about Euclid’s life, so creative measures were taken to create this book. Euclid’s Dilemma was written specifically with 7th grade students in mind. There are two Common Core State Standards for Mathematics that apply well to this story. They are: 7.G.A.1- Draw, construct, and describe geometrical figures and describe the relationships between them. 7.G.A.7- Solve real-life and mathematical problems involving angle measure, area, surface area, and volume.